Preventive Strategy of Responsibility for International Protection - Emiteg, Naser Benaros; Abokhres, Othman Omar (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to clarify the concept of ’Preventive Strategy’ in light of the responsibility for international protection. It has considered as the most important principle that (ICISS) committee tried to focus on as a basic stage that allows reducing or eliminating the need for military intervention. The success of the responsibility for prevention requires - in specific cases - a pressure from the international community. Consequently, a study problem arises in the questions, ’What is meant by Prevention of Responsibility for International Protection as Preventive Strategy? What is this Responsibility? What is its role in preventing conflicts? Moreover, it was necessary to demystify this concept, clarify its manifestations as well as its contribution to reduce the occurrence and exacerbations of conflicts. In addition to reviewing the most important mechanisms to activate them on international events. Therefore, the study followed the descriptive analytical approach. It studied and tracked the international texts and documents, reports and relevant decisions as well as analyzing them. All of these steps were for identifying the sublime role that responsibility for international prevention plays as a broader option than military operations in protecting and promoting human rights. Actually, the study concluded that the preventive strategy on which it is based the responsibility of international prevention is to search for the real causes that drive internal conflicts and human-made international crises, and the need to find solutions to prevent their occurrence. This can happen by adopting a set of preventive procedures and measures to help in promoting national development, to assist in implementation of developmental programs and to support local initiatives. Thus, these things would promote the cause of respect Human rights, strengthening the rule of law, contributing in development of good local administration, adopting good-offices and mediation, and promoting dialogue and reconciliation between the parties. Nevertheless, all of those could be achieved only through concerted local, regional and international efforts, as well as in coordination with the various bodies of the United Nations.